(untitled) (Fiep Bulletin - online, 2014)
Within the research project „Establishment of the system of monitoring physical fitness of students in physical education classes“ implemented by the Faculty of Sport and Physical Education in collaboration with the Institute for Assessment of Education Quality in Serbia from 2011-2014, the main aim was establishment of the system of monitoring physical fitness of students in elementary schools in Serbia. Based on this, we set the specific tasks: establishment of a physical fitness monitoring model for students that could be implemented in the Serbian educational system and the development of a battery of tests in that model. After setting up the physical fitness monitoring model for students, we proceeded with evaluation of appropriate battery of tests which could be applied in that model. After a theoretical analysis of certain batteries of tests, structurally fit to the physical fitness monitoring model for students applicable in our educational system, we selected a set of the most frequently applied tests of motor abilities. The assessment of reliability and sensitiveness of most frequently applied tests was performed in a sample of elementary school students from 3rd to 8th grade. In the same sample of students a test-retest method was applied – once in autumn and the second time in spring. In both cases remeasuring was carried after 15 days. The sample of subjects within the autumn testing involved 848 students (446 boys and 402 girls) attending elementary school, aged 9 to 14 years, while 834 students participated (444 boys and 390 girls) in the spring testing. The empirical research checked the reliability and sensitiveness of the following tests: 1600 m walk/run, 20 ? - Shuttle run, Standing long jump, Bent-arm hang, Sit-ups for 30 s, Sit and reach, High jump and Shuttle run 4x10 m. Based on the empirical verification of reliability and sensitivity of the most frequently applied tests in different models of physical fitness monitoring of children and youth worldwide, it can be concluded that they manifested satisfactory reliability and sensitiveness at all ages, in both genders from 3rd to 8thgrade of elementary school. Based on the evaluation of the most frequently applied tests in different models of physical fitness monitoring of children and youth worldwide, we proposed the battery of tests that fits the physical fitness monitoring model for students in the existing conditions for realization in physical education classes in Serbia.